Colonization of UK coastal realignment sites by mosquitoes: implications for design, management, and public health. Issue 1 (23rd May 2013) - Medlock, J.M.; Vaux, A.G.C.
ABSTRACT: Coastal realignment is now widely instituted in the UK as part of local flood risk management plans to compensate for the loss of European protected habitat and to mitigate the effects of sea‐level rise and coastal squeeze. Coastal aquatic habitats have long been known to provide suitable habitats for brackish‐water mosquitoes and historically, coastal marshes were considered to support anopheline mosquito populations that were responsible for local malaria transmission. This study surveyed the eight largest managed realignment (MRA) sites in England (Essex and the Humber) for mosquito habitats. The apparent absence of anopheline mosquitoes exploiting aquatic habitats at all of these sites suggests that the risk of malaria associated with MRA sites is currently negligible. However, three of the eight sites supported populations of two nuisance and potential arboviral vector species, Aedes detritus and Aedes caspius. The aquatic habitats that supported mosquitoes resulted from a) specific design aspects of the new sea wall (ballast to mitigate wave action and constructed saline borrow ditches) that could be designed out or managed or b) isolated pools created through silt accretion or expansion of flooded zones to neighbouring pasture. The public health risks and recommendations for management are discussed in this report. This report highlights the need for pro‐active public health impact assessments prior to MRA development in consultation with the Health Protection Agency, as well as the need for a case‐by‐case approach to design and management to mitigate mosquito or mosquito‐borne disease issues now and in the future.